Optimalisasi Pengelolaan Data Dan Notulensi Melalui Pelatihan Digitalisasi (PADI) Untuk Pemberdayaan Ibu-Ibu PKK - Cheppy Risnandar Angga Widjaya; Yoan Nurazizah; Sekar Asti Astuti; Nurjanah; Cindy Rahmawati; Siska Marlina; Lusy Meilani Nur’aeni Rohmah; Reza Deniarti; Lina Farhatun Nisa; Elit Pustikasari; Sonjaya Sonjaya; Khairil Fikri; Hisny Fajrussalam (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This article discusses using digital technology to increase administrative efficiency in community organizations such as the PKK. The service focuses on providing training in using Microsoft Word and Excel to PKK women in Pangauban Village to overcome manual administration challenges. The research method used is community-based participatory research (CBPR), which involves the active participation of service subjects. The results show an increase in participants' digital skills, efficiency in managing data and minutes, and an increase in participants' confidence in using technology. This program positively impacts the empowerment of PKK women and has the potential to develop technology initiatives at the village level.